2004
DOI: 10.1002/hep.20155
|View full text |Cite
|
Sign up to set email alerts
|

Progression of HCC in mice is associated with a downregulation in the expression of hepatocyte nuclear factors

Abstract: Hepatocyte nuclear factors (HNF) play a critical role in development of the liver. Their roles during liver tumorigenesis and progression of hepatocellular carcinomas (HCC) are, however, poorly understood. To address the role of HNFs in tumor progression, we generated a new experimental model in which a highly differentiated slow-growing transplantable mouse HCC (sgHCC) rapidly gives rise in vivo to a highly invasive fast-growing dedifferentiated variant (fgHCC). This in vivo model has allowed us to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
172
2
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 36 publications
(46 reference statements)
23
172
2
6
Order By: Relevance
“…A 1:20 dilution of starting chromatin DNA was used as PCR template for input normalization. hepatocytes, 18,19 re-establishes a differentiated phenotype to invasive hepatocellular carcinoma 19 and, as recently we demonstrated, controls the hepatic epithelial phenotype by direct repression of master EMT regulators including Snail. 2 MiRs-200 induce epithelial differentiation of cancer stem cells by direct targeting the transcriptional repressors of E-cadherin ZEB1 and ZEB2, and other stemness genes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A 1:20 dilution of starting chromatin DNA was used as PCR template for input normalization. hepatocytes, 18,19 re-establishes a differentiated phenotype to invasive hepatocellular carcinoma 19 and, as recently we demonstrated, controls the hepatic epithelial phenotype by direct repression of master EMT regulators including Snail. 2 MiRs-200 induce epithelial differentiation of cancer stem cells by direct targeting the transcriptional repressors of E-cadherin ZEB1 and ZEB2, and other stemness genes.…”
Section: Discussionsupporting
confidence: 64%
“…Our data are in line with previous evidences indicating these miRs as central factors of the regulation of epithelial phenotype. 19 Our results suggest the epistatic relationship depicted in Figure 6 in which transcriptional and post-transcriptional regulators are involved. The proposed mechanism implies that the execution of a stemness program requires the active repression of a differentiation program, whereas the maintenance of the hepatocyte one requires the active repression of stemness traits.…”
Section: Discussionsupporting
confidence: 56%
“…We showed expression of HNF4a to be well correlated with that of TCF2 and to be upregulated by inducing TCF2 expression using a methyltransferase inhibitor, which suggests alterations in the hepatocyte nuclear factor network can be reversed by inducing TCF2 through demethylation of the gene. Consistent with that idea, Lazarevich et al (2004) reported that expression of HNF4a is downregulated in hepatocellular carcinoma and its restoration suppresses tumour growth. It has also been reported that HNF4a is downregulated in other types of tumours (Lemm et al, 1999) and that it induces expression of endothelial Fas ligand (FasL), which prevents cancer cell transmigration (Osanai et al, 2002).…”
Section: Discussionsupporting
confidence: 57%
“…Expression of HNF4␣ is lost in a mouse model of hepatocellular carcinoma progression in which slow-growing tumors lose their epithelial characteristics and transform to a fast-growing invasive form. 144 Moreover, when expression of HNF4␣ is forced in the fast-growing invasive hepatocellular carcinoma cells, proliferation is reduced and tumor formation is suppressed. 144 In addition to controlling hepatocyte differentiation during embryogenesis, HNF4␣ is also required to maintain a differentiated hepatocyte phenotype, since disruption of Hnf4 in adult livers also dramatically affects hepatic gene expression and severely disrupts liver function.…”
Section: What Governs the Establishment Of Hepatic Architecture And Mmentioning
confidence: 99%
“…144 Moreover, when expression of HNF4␣ is forced in the fast-growing invasive hepatocellular carcinoma cells, proliferation is reduced and tumor formation is suppressed. 144 In addition to controlling hepatocyte differentiation during embryogenesis, HNF4␣ is also required to maintain a differentiated hepatocyte phenotype, since disruption of Hnf4 in adult livers also dramatically affects hepatic gene expression and severely disrupts liver function. 135 Although the data still need to be validated by genetic analyses, when chromatin immunoprecipitation was used to probe human promoter microarrays for HNF4␣ DNA elements within HepG2 cells, HNF4␣ was shown to occupy a surprising 12% (1,575 genes) of genes represented on the Hu13K microarray.…”
Section: What Governs the Establishment Of Hepatic Architecture And Mmentioning
confidence: 99%